The Influence of Using ChatGPT on Students’ Narrative Writing at MTs N 1 Pesawaran - Fitri, Desi Ririanti; Muhassin, Mohammad; Nawawi, Muhammad (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This research explores the impact of incorporating ChatGPT into students' narrative writing abilities at MTs N 1 Pesawaran. It employs a quasi-experimental approach with a pre-test and post-test setup across two groups: an experimental class and a control class. The experimental group received instruction on narrative writing supported by ChatGPT, while the control group followed traditional teaching methods. Writing tests were used to gather data, which was then analyzed statistically, including checks for normality, homogeneity, and t-tests. The results reveal that students in the experimental class scored significantly higher on the post-test than those in the control class. These findings imply that ChatGPT can be a valuable resource for boosting students' writing skills, especially in structuring ideas, expanding vocabulary, and crafting well-organized narrative texts.